1925 Ind. Acts 499 § 13 - (:unkn) unknown (General Publisher, 1925)
Prohibited changing, altering, removing, or obliterating identifying information on any pistol or revolver. Possession of such arms is a misdemeanor, punished by imprisonment for not less than six months nor more than one year.
--
Keywords: DEFACED FIREARMS